Water-based heat-resistant coating as well as preparation method and application thereof

By using ionic liquid-graphene oxide doped silicone-modified acrylic resin in heat-resistant coatings, combined with other additives, the problem of insufficient performance of water-based heat-resistant coatings in complex environments is solved, achieving high adhesion and salt resistance. Comprehensive improvement of fog properties and excellent heat resistance.

CN119331478APending Publication Date: 2025-01-21BBMG WEIGUAN (CANGZHOU) CHEM CO LTD

Patent Information

Application Number
CN202411626076.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

During the water-bearing conversion process, existing heat-resistant coatings are difficult to meet the needs of high adhesion, salt spray resistance and excellent heat resistance at the same time, especially in complex environments such as rotary kilns.

Method used

Ionic liquid-graphene oxide doped silicone-modified acrylic resin is used as a water-based resin to inhibit the agglomeration of graphene oxide through strong hydrogen bonds and improve the thermal stability and anti-corrosion properties of the material. It is also combined with other additives such as rutile titanium dioxide, Carbon black, talc powder, mica powder, etc., adjust viscosity and performance.

Benefits of technology

It realizes the high adhesion, salt -resistant and excellent heat -resistant performance of water -based heat -resistant coatings, and is suitable for the application of high temperature and complex environments such as rotating kiln.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a water-based heat-resistant coating as well as a preparation method and application thereof. Relates to the technical field of water-based heat-resistant coating preparation. The ionic liquid-graphene oxide doped organic silicon modified acrylic resin is used as water-based resin, and the thermal stability, adhesive force and corrosion resistance of the coating are improved through the synergistic effect of phosphate radicals brought by graphene oxide and ionic liquid and auxiliaries added in the coating preparation process. The water-based heat-resistant coating is high in adhesive force, good in salt fog resistance and excellent in heat resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water-based heat-resistant coating preparation, and in particular to a water-based heat-resistant coating, a preparation method and an application thereof. Background Art

[0002] As a special category, heat-resistant coatings have important applications in specific fields. Due to their good heat resistance and corrosion resistance, they are widely used in fields with temperature operations.

[0003] Under the current development situation, my country's coatings industry is vigorously promoting water-based products. The field of heat-resistant coatings is inevitably facing the same demand for water-based products. Water-based products have many advantages and necessities. On the one hand, water-based heat-resistant coatings can reduce the use of organic solvents and reduce pollution to the environment, which is in line with the current development concept of green environmental protection. During the construction process, water-based coatings release very few volatile organic compounds (VOCs), which helps to improve the working environment of construction workers and protect their health. On the other hand, as people's attention to environmental protection and sustainable development continues to increase, the market demand for water-based heat-resistant coatings is also gradually increasing. Many industries, such as automobiles, aerospace, electronics, etc., have higher and higher performance requirements for heat-resistant coatings, and also put forward higher requirements for environmental protection. Water-based heat-resistant coatings just meet the needs of these industries, providing them with a solution that has both excellent heat resistance and environmental protection.

[0004] In addition, water-based paint also has good adhesion and can firmly adhere to the surface of various substrates, such as metal, ceramic, glass, etc. It is not easy to peel or peel off, providing reliable protection for the substrate. Good heat resistance, can maintain good coating integrity and performance stability in high temperature environment, has a high heat-resistant temperature range, and can meet the needs of different high-temperature working conditions. Strong corrosion resistance, good tolerance to chemical substances such as acid, alkali, and salt, can protect the substrate in harsh chemical environments and extend the service life of objects. Good mechanical properties, after film formation, it has good mechanical properties, such as impact strength, flexibility, hardness and other indicators can reach a good level, which can effectively resist external mechanical shock and wear.

[0005] In the field of rotary kilns, heat-resistant coatings have been used for a long time. However, the operation of rotary kilns is accompanied by vibrations, which requires the coating to have better adhesion. At the same time, the improvement of salt spray resistance is also more conducive to the long-term protection of the coating. Therefore, there is an urgent need for a heat-resistant coating used in the field of rotary kilns, which must meet the needs of water-based, have high adhesion, good salt spray resistance, and excellent heat resistance. Summary of the invention

[0006] In view of the technical problems existing in the prior art, the present invention aims to provide a water-based heat-resistant coating, a preparation method and an application thereof.

[0007] One of the purposes of the present invention is to provide a water-based heat-resistant coating, which comprises the following raw materials in parts by weight: 40~50 parts of water-based resin Pigment 10~20 parts Filler 8~15 parts 5~10 parts of anti-rust material Dispersant 0.7~1.7 parts Defoaming agent 0.5~0.7 parts Leveling agent 0.4~0.6 parts Anti-flash rust agent 0.4~0.8 parts Thickener 0.3~0.6 parts Film former 1.5~2.5 parts 3~5 parts of organic solvent 10-20 parts water; Wherein, the water-based resin is an ionic liquid-graphene oxide doped silicone-modified acrylic resin.

[0008] Preferably, the preparation method of the ionic liquid-graphene oxide doped organosilicon-modified acrylic resin comprises: An initiator is added to a mixed monomer solution of methyl acrylate, styrene, hydroxyethyl methacrylate and acrylic acid, and the mixture is uniformly mixed and then dripped into a mixed solvent of polydimethylsiloxane, ethyl acetate and butyl acetate to carry out a free radical copolymerization reaction, thereby obtaining a water-based organosilicon-modified acrylic resin; The ionic liquid and graphene oxide are mixed and then ground to obtain ionic liquid-graphene oxide, and the ionic liquid-graphene oxide is added to a water-based organosilicon-modified acrylic resin and then dispersed to obtain an ionic liquid-graphene oxide-doped water-based organosilicon-modified acrylic resin.

[0009] Preferably, the initiator comprises dibenzoyl peroxide.

[0010] Preferably, the dropping speed is 200-400 mL / h.

[0011] Preferably, the grinding time is 2 to 6 hours.

[0012] Preferably, ultrasonic dispersion is used for dispersion.

[0013] Preferably, the ionic liquid contains phosphate ions.

[0014] Preferably, the concentration of phosphate ions is 1% to 3%.

[0015] Preferably, the ionic liquid comprises tributylamine phosphate and / or triethylamine phosphate.

[0016] Preferably, the mass ratio of the ionic liquid to the graphene oxide is 15-30:1.

[0017] Preferably, the mass ratio of the ionic liquid-graphene oxide to the water-based organosilicon-modified acrylic resin is 1:20-100.

[0018] Preferably, the pigment comprises rutile titanium dioxide and / or carbon black; The filler includes one or more of talc powder, precipitated barium sulfate or mica powder; Anti-rust materials include inorganic anti-corrosion materials; Flash rust inhibitors include organic zinc chelates; Dispersants include nonionic wetting and dispersing agents; Defoamers include polyether siloxane defoamers; Leveling agents include polyether siloxane copolymer leveling agents; The film former includes one or more of ethylene glycol, propylene glycol or dodecyl alcohol ester; The thickener includes a polyurethane thickener and / or a polyacrylic thickener; The organic solvent includes propylene glycol methyl ether and / or propylene glycol diacetate.

[0019] A second object of the present invention is to provide a method for preparing a water-based heat-resistant coating, the preparation method comprising: The water, dispersant, defoamer, pigment, filler and rust-proof material are mixed uniformly and ground to a fineness of ≤30 μm to obtain a water slurry; the stirring speed is 1000-1250 rpm; Add water-based resin into a container, add anti-flash rust agent, film-forming agent, water slurry, organic solvent and leveling agent under the condition of stirring at a rate of 600-800 rpm, stir evenly, add thickener to adjust viscosity, and obtain the product.

[0020] A third object of the present invention is to provide an application of a water-based heat-resistant coating on a rotary kiln.

[0021] Beneficial effects of the present invention: The present invention provides a water-based heat-resistant coating, which uses an organosilicon-modified acrylic resin doped with ionic liquid-graphene oxide as a water-based resin. Graphene oxide has a special lamellar structure similar to graphene, and because its hexagonal carbon ring base plane is oxidized by a strong acid, there are particularly rich hydroxyl and carboxyl functional groups in its plane. It is precisely because of its large number of hydrophilic functional groups that it can effectively improve the hydrophilicity of polymer materials and related properties such as corrosion resistance. However, graphene oxide is easy to agglomerate. Therefore, an ionic liquid containing phosphate anions and graphene oxide are mixed, and the strong hydrogen bonding between the phosphate anions and graphene oxide is used to effectively inhibit the agglomeration of graphene oxide. The hydrogen bond can also be used as an additional energy absorption mode to improve the thermal stability of the material to a certain extent. In addition, the phosphate in the ionic liquid can further increase its corrosion resistance. The water-based heat-resistant coating has strong adhesion, good salt spray resistance, and excellent heat resistance. DETAILED DESCRIPTION

[0022] According to the first aspect of the present invention, a water-based heat-resistant coating is provided, wherein the water-based heat-resistant coating comprises the following raw materials in parts by weight: 40~50 parts of water-based resin Pigment 10~20 parts Filler 8~15 parts 5~10 parts of anti-rust material Dispersant 0.7~1.7 parts Defoaming agent 0.5~0.7 parts Leveling agent 0.4~0.6 parts Anti-flash rust agent 0.4~0.8 parts Thickener 0.3~0.6 parts Film former 1.5~2.5 parts 3~5 parts of organic solvent 10-20 parts water; Wherein, the water-based resin is an ionic liquid-graphene oxide doped silicone-modified acrylic resin.

[0023] In the present invention, an ionic liquid-graphene oxide doped organosilicon-modified acrylic resin is used as a water-based resin. Graphene oxide has a special sheet structure similar to graphene, and because its hexagonal carbon ring base plane is oxidized by a strong acid, there are particularly abundant hydroxyl and carboxyl functional groups in its plane. It is precisely because of its large number of hydrophilic functional groups that it can effectively improve the hydrophilicity and anti-corrosion related properties of polymer materials. The acid radical ions in the ionic liquid can form strong hydrogen bonds with graphene oxide, effectively inhibiting the agglomeration of graphene oxide.

[0024] Hydrogen bonds can also be used as an additional energy absorption method to improve the thermal stability of the material to a certain extent. Graphene oxide also has high thermal stability, which can support and stabilize the coating structure at high temperatures. The silicone component can provide good heat resistance in the resin. The silicone segment has high bond energy and thermal stability, and can maintain a good chemical structure in a high temperature environment to prevent the coating from decomposing prematurely.

[0025] Silicone-modified acrylic resin itself has good adhesion, and it can form good adhesion on the surface of various substrates. Graphene oxide has a high specific surface area and excellent physical and chemical properties. Its doping in the resin can enhance the physical adsorption and chemical bonding between the resin and the substrate.

[0026] The sheet structure of graphene oxide can act as a physical barrier to delay the corrosion of the coating by salt spray. The silicone-modified acrylic resin itself has a certain chemical resistance and can resist chemical reactions in the salt spray environment.

[0027] The weight of the aqueous resin is, for example, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts or 50 parts.

[0028] In the present invention, the weight of the pigment is, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.

[0029] In the present invention, the weight of the filler is, for example, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts or 15 parts.

[0030] In the present invention, the weight of the rust-proof material is, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.

[0031] In the present invention, the weight of the dispersant is, for example, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts or 1.7 parts.

[0032] In the present invention, the weight of the defoaming agent is, for example, 0.5 part, 0.55 part, 0.6 part, 0.65 part or 0.7 part.

[0033] In the present invention, the weight of the leveling agent is, for example, 0.4 part, 0.45 part, 0.5 part, 0.55 part or 0.6 part.

[0034] In the present invention, the weight of the flash rust inhibitor is, for example, 0.4 part, 0.45 part, 0.5 part, 0.55 part, 0.6 part, 0.65 part, 0.7 part, 0.75 part or 0.8 part.

[0035] In the present invention, the weight of the thickener is, for example, 0.3 part, 0.35 part, 0.4 part, 0.45 part, 0.5 part, 0.55 part or 0.6 part.

[0036] In the present invention, the weight of the film-forming agent is, for example, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2.0 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts or 2.5 parts.

[0037] In the present invention, the weight of the organic solvent is, for example, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts or 5.0 parts.

[0038] In a preferred embodiment of the present invention, the preparation method of the ionic liquid-graphene oxide doped organosilicon-modified acrylic resin comprises: Dibenzoyl peroxide initiator is added to a mixed solution of methyl acrylate, styrene, hydroxyethyl methacrylate and acrylic acid, and after uniform mixing, the mixture is added dropwise to a mixed solvent of polydimethylsiloxane, ethyl acetate and butyl acetate for free radical copolymerization at a dropping speed of 200-400 mL / h to obtain a water-based organosilicon-modified acrylic resin; The ionic liquid and graphene oxide were mixed and ground for 2 to 6 hours to prepare ionic liquid-graphene oxide, and the ionic liquid-graphene oxide was added to a water-based organosilicon-modified acrylic resin and then ultrasonically dispersed to obtain an ionic liquid-graphene oxide-doped water-based organosilicon-modified acrylic resin.

[0039] In the present invention, the total mass of the hydroxyethyl methacrylate and acrylic acid accounts for 10-30% of the entire polymerization reaction system, and the initiator accounts for 0.5%-1% of the total mass of the mixed monomers.

[0040] In the present invention, polydimethylsiloxane accounts for 5%-10% of the mixed solvent, ethyl acetate and butyl acetate account for 60%-80% of the mixed solvent, and the mass ratio of polydimethylsiloxane to ethyl acetate and butyl acetate is 0.5-2:1.

[0041] In a preferred embodiment of the present invention, the ionic liquid contains phosphate ions. Strong hydrogen bonds can be formed between phosphate anions and graphene oxide, including P-O-H...O (graphene oxide) hydrogen bonds and P=O...H-O (graphene oxide) hydrogen bonds. Strong hydrogen bonds can effectively inhibit the agglomeration of graphene oxide, make graphene oxide uniformly dispersed, and improve material properties. Phosphate ions can react with iron ions to form a dense oxide protective film to prevent further corrosion by chloride ions and other ions in salt spray.

[0042] In a preferred embodiment of the present invention, the concentration of phosphate ions is 1% to 3%.

[0043] In the present invention, phosphate ions can interact with components such as silicone-modified acrylic resin and graphene oxide to form a cross-linked structure. This cross-linked structure can enhance the bonding force between the coating and the coated substrate, thereby improving adhesion. If the phosphate ion concentration is too low, sufficient cross-linking may not be formed, resulting in an insignificant adhesion improvement effect; while if the concentration is too high, excessive cross-linking may make the coating too hard and brittle, which in turn affects its adhesion performance on the substrate. Phosphate ions have a certain anti-corrosion effect. An appropriate amount of phosphate ions can synergize with rust-proof materials in the coating to form a dense protective film on the surface of the metal substrate, preventing the intrusion of corrosive substances such as salt, thereby improving the salt spray resistance of the coating. When the concentration is 1% - 3%, this synergistic anti-corrosion effect can be better exerted; if the concentration is too low, the anti-corrosion effect is insufficient, and too high a concentration may cause unevenness of the film layer or other side effects, affecting the salt spray resistance. Phosphate ions interact with other components in the coating, which helps to improve the thermal stability of the entire system. In the concentration range of 1%-3%, this effect can achieve a good balance, so that the coating maintains good performance in high temperature environment. If the concentration is too low, the effect of improving thermal stability is not obvious; if the concentration is too high, the stability of the coating system will deteriorate, and precipitation and stratification will occur. This is because too many phosphate ions may react or interact excessively with other components, destroying the original structure and stability of the coating. It will also make the coating film too hard and brittle, reduce flexibility, and easily crack and peel when subjected to external force or thermal stress, thereby reducing the adhesion, salt spray resistance and heat resistance of the coating.

[0044] In a preferred embodiment of the present invention, the ionic liquid comprises tributylamine phosphate or triethylamine phosphate.

[0045] In a preferred embodiment of the present invention, the mass ratio of the ionic liquid to the graphene oxide is 15-30:1.

[0046] In the present invention, within the mass ratio range of 15-30:1, the ionic liquid and graphene oxide can synergistically improve the comprehensive performance of the coating. The ionic liquid can help the graphene oxide to disperse evenly, give full play to the advantages of graphene oxide such as high specific surface area, good barrier properties and enhanced mechanical properties, while ensuring the stability of the system and the performance of other functions, and improving adhesion, salt spray resistance and heat resistance.

[0047] When the mass ratio is less than 15:1, graphene oxide tends to aggregate in the coating system. Due to its large specific surface area, when the content is high, the van der Waals force between the flakes causes it to aggregate and cannot be evenly dispersed, resulting in the failure to fully exert its advantages such as high barrier properties and enhanced adhesion. It will also cause defects due to agglomeration, which will reduce salt spray resistance, adhesion and heat resistance. At the same time, graphene oxide is expensive, and excessive use will significantly increase costs and reduce product competitiveness. In addition, too much graphene oxide will change the rheological properties of the coating, greatly increase viscosity or even lose fluidity, which will bring difficulties to construction.

[0048] If the mass ratio is greater than 30:1, too much ionic liquid will dilute the effective concentration of graphene oxide and weaken its enhancement effect on the coating performance, such as reducing the contribution to the coating barrier performance (related to salt spray resistance) and mechanical properties (related to adhesion and heat resistance), making the overall performance of the coating unable to meet the requirements of high adhesion, good salt spray resistance and excellent heat resistance. Moreover, too much ionic liquid may affect the drying and curing process of the coating, resulting in prolonged drying time and reduced film quality, which in turn affects properties such as adhesion, because it will interfere with the normal function of the film-forming agent and make the density and stability of the coating worse.

[0049] In the present invention, the mass ratio of the ionic liquid to graphene oxide is preferably 22:1.

[0050] In a preferred embodiment of the present invention, the mass ratio of the ionic liquid-graphene oxide to the water-based organosilicon-modified acrylic resin is 1:20-100.

[0051] In the present invention, the ionic liquid-graphene oxide composite can effectively modify the waterborne silicone modified acrylic resin. A sufficient amount of resin can ensure good film-forming properties and lay the foundation for high adhesion. It can form a continuous coating on the surface of the substrate and tightly bond with the substrate. An appropriate amount of the composite can improve salt spray resistance and heat resistance. The hydrophilic barrier property of graphene oxide and the anticorrosive property of the phosphate group in the ionic liquid can synergistically enhance the protective performance with the resin. Considering the stability of the system, this mass ratio helps to maintain the stability of the coating and avoid excessive changes in viscosity due to improper ratios, which affects storage and construction performance.

[0052] If the mass ratio is less than 1:20, too much ionic liquid-graphene oxide will destroy the film-forming properties. Too much compound will interfere with the normal film-forming of the resin, causing defects such as increased porosity and uneven surface in the coating, reducing adhesion, making it easier for salt spray to penetrate, reducing salt spray resistance, and making the integrity of the coating more easily damaged at high temperatures, and deteriorating heat resistance. In terms of construction and storage, the viscosity of the coating will increase significantly and even become a paste, making it difficult to apply, such as being unable to spray or brush normally. During storage, the stability of the system will be destroyed, and it will be easy to precipitate and agglomerate, shortening the shelf life.

[0053] When the mass ratio is greater than 1:100, the ionic liquid-graphene oxide is too little, and the ionic liquid-graphene oxide has limited effect on enhancing the performance of the coating. It is unable to give full play to the barrier and enhancement of graphene oxide and the anti-corrosion advantages of the phosphate in the ionic liquid. The salt spray resistance and heat resistance are not significantly improved, and it is difficult to meet the high protection performance requirements. The performance of the coating is greatly reduced in a high-demand environment. In terms of modification, its content is too low, and it is almost impossible to modify the resin. The coating performance is close to that of the unmodified resin coating, and it cannot meet the requirements of high adhesion, salt spray resistance and heat resistance in specific application scenarios.

[0054] In the present invention, the mass ratio of the ionic liquid-graphene oxide to the water-based organosilicon-modified acrylic resin is preferably 1:60.

[0055] In a preferred embodiment of the present invention, the pigment comprises rutile titanium dioxide and / or carbon black; The filler includes one or more of talc powder, precipitated barium sulfate or mica powder; Anti-rust materials include inorganic anti-corrosion materials; Flash rust inhibitors include organic zinc chelates; Dispersants include nonionic wetting and dispersing agents; Defoamers include polyether siloxane defoamers; Leveling agents include polyether siloxane copolymer leveling agents; The film former includes one or more of ethylene glycol, propylene glycol or dodecyl alcohol ester; The thickener includes a polyurethane thickener and / or a polyacrylic thickener; The organic solvent includes propylene glycol methyl ether and / or propylene glycol diacetate.

[0056] In the present invention, the rutile titanium dioxide includes 868 or 2195, preferably 868; The carbon black includes B4210 or 9428A, preferably 9428A; The talc powder includes 3000 mesh talc powder, 1250 mesh talc powder, 800 mesh talc powder or 400 mesh talc powder, preferably 1250 mesh talc powder; The precipitated barium sulfate includes 3000 mesh precipitated barium sulfate, 1250 mesh precipitated barium sulfate, 800 mesh precipitated barium sulfate or 325 mesh precipitated barium sulfate, preferably 1250 mesh precipitated barium sulfate; The mica powder includes GA-4, GB-2 or GB-3, preferably GA-4; The inorganic preservative comprises ZPL2 or L2, preferably L2; The organic zinc chelate anti-flash rust agent includes FA179 or FA180, preferably FA179; The nonionic wetting and dispersing agent includes TEGO760W or TEGO755W, preferably TEGO755W; The polyether siloxane defoamer includes TEGO810, TEGO845 or TEGO906W, preferably TEGO810; The polyether siloxane copolymer includes TEGO450, TEGO496 or TEGO498, preferably TEGO450; The thickener includes 0620, U605 or 299, preferably 0620.

[0057] In the present invention, the particle size and surface properties of rutile titanium dioxide can help fill the tiny gap between the resin and the substrate, increase the contact area, and thus improve the adhesion. The high dispersibility and good compatibility of carbon black with the resin also help to enhance the adhesion of the coating as a whole. The dispersant can make the pigment and filler dispersed evenly in the resin. A good dispersion state helps the coating to level better during the coating process, making the contact between the coating and the substrate more close and even, thereby improving the adhesion.

[0058] Inorganic preservatives can form a corrosion-resistant protective layer inside or on the surface of the coating, effectively preventing salt spray corrosion. In a salt spray environment, metal substrates are prone to flash rust. Organic zinc chelate anti-flash rust agents can form a protective film on the metal surface to inhibit the initial corrosion of the metal, thereby improving the salt spray resistance of the entire coating system. Good leveling can make the coating surface smoother and reduce defects on the coating surface (such as pinholes, bubbles, etc.). In a salt spray environment, these defects can easily become channels for salt spray erosion, so the leveling agent improves the salt spray resistance by improving the surface quality of the coating.

[0059] Talc can improve the hardness, scratch resistance and filling performance of the coating, make the coating more dense, and enhance the protection of the substrate; precipitated barium sulfate can improve the hiding power and chemical stability of the coating, and better maintain the coating performance in a complex environment; mica powder has a flaky structure, which can effectively improve the barrier properties of the coating, such as preventing the penetration of water vapor, salt, etc., while enhancing the weather resistance and heat resistance of the coating. Fillers can improve the heat resistance of the coating to a certain extent. The flaky structure of mica powder can form a structure similar to an "insulating layer" in the coating to block the transfer of heat. The high specific gravity and chemical stability of precipitated barium sulfate also help to improve the heat resistance of the coating, and can reduce the shrinkage and deformation of the coating at high temperatures.

[0060] According to the second aspect of the present invention, a method for preparing a water-based heat-resistant coating is provided, the preparation method comprising: The water, dispersant, defoamer, pigment, filler and rust-proof material are mixed uniformly and ground to a fineness of ≤30 μm to obtain a water slurry; the stirring speed is 1000-1250 rpm; Add water-based resin into a container, add anti-flash rust agent, film-forming agent, water slurry, organic solvent and leveling agent under the condition of stirring at a rate of 600-800 rpm, stir evenly, add thickener to adjust viscosity, and obtain the product.

[0061] The third object of the present invention is to provide an application of the water-based heat-resistant coating as described above in a rotary kiln.

[0062] Example 1 The preparation method of the ionic liquid-graphene oxide doped organosilicon-modified acrylic resin in this embodiment is as follows: 0.05 part of dibenzoyl peroxide initiator was added to a mixed solution of 35 parts of methyl acrylate, 40 parts of styrene, 10 parts of hydroxyethyl methacrylate and 15 parts of acrylic acid, and then the mixture was uniformly mixed and then dropped into a mixed solvent of 15 parts of polydimethylsiloxane, 200 parts of ethyl acetate and 200 parts of butyl acetate to carry out a free radical copolymerization reaction at a dropping speed of 200-400 mL / h to obtain a water-based organosilicon-modified acrylic resin; 22 parts of tributylamine phosphate and 1 part of graphene oxide were mixed and ground for 4 hours to prepare ionic liquid-graphene oxide; 1 part of ionic liquid-graphene oxide was added to 60 parts of water-based silicone-modified acrylic resin and then ultrasonically dispersed to obtain ionic liquid-graphene oxide-doped water-based silicone-modified acrylic resin.

[0063] The water-based heat-resistant coating of this embodiment includes the following raw materials in parts by weight: 40.0 parts of ionic liquid-graphene oxide doped silicone modified acrylic resin, 13.0 parts of rutile titanium dioxide 8681, 1.5 parts of carbon black 9428A, 3.0 parts of 1250 mesh talc, 8.0 parts of mica powder GA-4, 4.0 parts of 1250 mesh precipitated barium sulfate, 9.0 parts of inorganic preservative L2, 0.5 parts of polyether siloxane defoamer TEGO810, 0.8 parts of non-ionic wetting and dispersing agent TEGO755W, 0.6 parts of polyether siloxane copolymer TEGO450, 0.4 parts of organic zinc chelate anti-flash rust agent FA179, 0.4 parts of polyurethane thickener 0620, 2.0 parts of propylene glycol, 3.5 parts of propylene glycol methyl ether and 13.3 parts of water.

[0064] The preparation method of the water-based heat-resistant coating provided in this embodiment is: The water, dispersant, defoamer, pigment, filler and rust-proof material are mixed evenly and then ground to a fineness of ≤30 μm to obtain a water slurry; Add water-based resin into a container, add anti-rust agent, film-forming agent, water slurry, organic solvent and leveling agent during stirring, add thickener to adjust viscosity after stirring evenly, and obtain the product.

[0065] Example 2 The water-based heat-resistant coating of this embodiment includes the following raw materials in parts by weight: 43.0 parts of ionic liquid-graphene oxide doped silicone modified acrylic resin, 19.0 parts of rutile titanium dioxide, 0.2 parts of carbon black, 2.0 parts of talc, 5.0 parts of mica powder, 3.0 parts of precipitated barium sulfate, 7.0 parts of inorganic preservatives, 0.6 parts of polyether siloxane defoamer, 1.2 parts of nonionic wetting and dispersing agent, 0.6 parts of polyether siloxane copolymer, 0.6 parts of organic zinc chelate anti-flash rust agent, 0.5 parts of polyurethane thickener, 2.5 parts of dodecyl alcohol ester, 4.0 parts of propylene glycol diacetate and 10.8 parts of water.

[0066] The rest is the same as Example 1.

[0067] Example 3 The water-based heat-resistant coating of this embodiment includes the following raw materials in parts by weight: 48.0 parts of ionic liquid-graphene oxide doped silicone modified acrylic resin, 15.5 parts of rutile titanium dioxide, 0.8 parts of carbon black, 2.0 parts of talc, 4.0 parts of mica powder, 2.0 parts of precipitated barium sulfate, 5.0 parts of inorganic preservatives, 0.5 parts of polyether siloxane defoamer, 1.3 parts of nonionic wetting and dispersing agent, 0.4 parts of polyether siloxane copolymer, 0.4 parts of organic zinc chelate anti-flash rust agent, 0.5 parts of polyurethane thickener, 2.0 parts of dodecyl alcohol ester, 3.0 parts of propylene glycol diacetate and 14.6 parts of water.

[0068] The rest is the same as Example 1.

[0069] Example 4 The water-based heat-resistant coating of this embodiment includes the following raw materials in parts by weight: 50.0 parts of ionic liquid-graphene oxide doped silicone modified acrylic resin, 16.5 parts of rutile titanium dioxide, 0.8 parts of carbon black, 2.0 parts of talc, 3.0 parts of mica powder, 2.0 parts of precipitated barium sulfate, 5.0 parts of inorganic preservatives, 0.5 parts of polyether siloxane defoamer, 1.3 parts of nonionic wetting and dispersing agent, 0.4 parts of polyether siloxane copolymer, 0.4 parts of organic zinc chelate anti-flash rust agent, 0.5 parts of polyurethane thickener, 2.0 parts of dodecyl alcohol ester, 3.0 parts of propylene glycol diacetate and 12.6 parts of water.

[0070] The rest is the same as Example 1.

[0071] Example 5 In the preparation method of the ionic liquid-graphene oxide doped silicone-modified acrylic resin in this embodiment, 15 parts of tributylamine phosphate and 1 part of graphene oxide are mixed and ground for 4 hours to prepare the ionic liquid-graphene oxide; 1 part of the ionic liquid-graphene oxide is added to 60 parts of water-based silicone-modified acrylic resin and then ultrasonically dispersed to obtain the ionic liquid-graphene oxide doped water-based silicone-modified acrylic resin.

[0072] The rest is the same as Example 3.

[0073] Example 6 In the preparation method of the ionic liquid-graphene oxide doped silicone-modified acrylic resin in this embodiment, 30 parts of tributylamine phosphate and 1 part of graphene oxide are mixed and ground for 4 hours to prepare the ionic liquid-graphene oxide; 1 part of ionic liquid-graphene oxide is added to 60 parts of water-based silicone-modified acrylic resin and then ultrasonically dispersed to obtain the ionic liquid-graphene oxide doped water-based silicone-modified acrylic resin.

[0074] The rest is the same as Example 3.

[0075] Example 7 In the preparation method of the ionic liquid-graphene oxide doped silicone-modified acrylic resin in this embodiment, 22 parts of tributylamine phosphate and 1 part of graphene oxide are mixed and ground for 4 hours to prepare the ionic liquid-graphene oxide; 1 part of ionic liquid-graphene oxide is added to 20 parts of water-based silicone-modified acrylic resin and then ultrasonically dispersed to obtain the ionic liquid-graphene oxide doped water-based silicone-modified acrylic resin.

[0076] The rest is the same as Example 3.

[0077] Example 8 In the preparation method of the ionic liquid-graphene oxide doped silicone-modified acrylic resin in this embodiment, 22 parts of tributylamine phosphate and 1 part of graphene oxide are mixed and ground for 4 hours to prepare the ionic liquid-graphene oxide; 1 part of the ionic liquid-graphene oxide is added to 100 parts of water-based silicone-modified acrylic resin and then ultrasonically dispersed to obtain the ionic liquid-graphene oxide doped water-based silicone-modified acrylic resin.

[0078] The rest is the same as Example 3.

[0079] Comparative Example 1 30.0 parts of ionic liquid-graphene oxide doped silicone modified acrylic resin, 17.5 parts of rutile titanium dioxide, 2.0 parts of carbon black, 4.0 parts of talc, 9.0 parts of mica powder, 3.0 parts of precipitated barium sulfate, 9.0 parts of inorganic preservatives, 0.5 parts of polyether siloxane defoamer, 1.3 parts of nonionic wetting and dispersing agent, 0.4 parts of polyether siloxane copolymer, 0.4 parts of organic zinc chelate anti-flash rust agent, 0.5 parts of polyurethane thickener, 2.0 parts of dodecyl alcohol ester, 3.0 parts of propylene glycol diacetate and 17.4 parts of water.

[0080] The rest is the same as Example 1.

[0081] Comparative Example 2 60.0 parts of ionic liquid-graphene oxide doped silicone modified acrylic resin, 12.5 parts of rutile titanium dioxide, 0.4 parts of carbon black, 1.0 parts of talc, 2.0 parts of mica powder, 0.8 parts of precipitated barium sulfate, 2.2 parts of inorganic preservatives, 0.5 parts of polyether siloxane defoamer, 1.3 parts of nonionic wetting and dispersing agent, 0.4 parts of polyether siloxane copolymer, 0.4 parts of organic zinc chelate anti-flash rust agent, 0.5 parts of polyurethane thickener, 2.0 parts of dodecyl alcohol ester, 3.0 parts of propylene glycol diacetate and 13 parts of water.

[0082] The rest is the same as Example 1.

[0083] Comparative Example 3 In the preparation method of the ionic liquid-graphene oxide doped silicone-modified acrylic resin in this embodiment, 10 parts of tributylamine phosphate and 1 part of graphene oxide are mixed and ground for 4 hours to prepare the ionic liquid-graphene oxide; 1 part of the ionic liquid-graphene oxide is added to 60 parts of water-based silicone-modified acrylic resin and then ultrasonically dispersed to obtain the ionic liquid-graphene oxide doped water-based silicone-modified acrylic resin.

[0084] The rest is the same as Example 3.

[0085] Comparative Example 4 In the preparation method of the ionic liquid-graphene oxide doped silicone-modified acrylic resin in this embodiment, 35 parts of tributylamine phosphate and 1 part of graphene oxide are mixed and ground for 4 hours to prepare the ionic liquid-graphene oxide; 1 part of the ionic liquid-graphene oxide is added to 60 parts of water-based silicone-modified acrylic resin and then ultrasonically dispersed to obtain the ionic liquid-graphene oxide doped water-based silicone-modified acrylic resin.

[0086] The rest is the same as Example 3.

[0087] Comparative Example 5 In the preparation method of the ionic liquid-graphene oxide doped silicone-modified acrylic resin in this embodiment, 22 parts of tributylamine phosphate and 1 part of graphene oxide are mixed and ground for 4 hours to prepare the ionic liquid-graphene oxide; 1 part of ionic liquid-graphene oxide is added to 15 parts of water-based silicone-modified acrylic resin and then ultrasonically dispersed to obtain the ionic liquid-graphene oxide doped water-based silicone-modified acrylic resin.

[0088] The rest is the same as Example 3.

[0089] Comparative Example 6 In the preparation method of the ionic liquid-graphene oxide doped silicone-modified acrylic resin in this embodiment, 22 parts of tributylamine phosphate and 1 part of graphene oxide are mixed and ground for 4 hours to prepare the ionic liquid-graphene oxide; 1 part of ionic liquid-graphene oxide is added to 110 parts of water-based silicone-modified acrylic resin and then ultrasonically dispersed to obtain the ionic liquid-graphene oxide doped water-based silicone-modified acrylic resin.

[0090] The rest is the same as Example 3.

[0091] Performance Testing Table 1 Performance test standards

[0092] Table 2 Performance test results of Examples 1 to 8

[0093] Table 3 Performance test results of comparative examples 1 to 6

Claims

1. A water-based heat-resistant coating, characterized in that: The water-based heat-resistant coating comprises the following raw materials in parts by weight: 40~50 parts of water-based resin Pigment 10~20 parts Filler 8~15 parts 5~10 parts of anti-rust material Dispersant 0.7~1.7 parts Defoaming agent 0.5~0.7 parts Leveling agent 0.4~0.6 parts Anti-flash rust agent 0.4~0.8 parts Thickener 0.3~0.6 parts Film former 1.5~2.5 parts 3~5 parts of organic solvent 10-20 parts water; Wherein, the water-based resin is an ionic liquid-graphene oxide doped silicone-modified acrylic resin.

2. The water-based heat-resistant coating according to claim 1, characterized in that: The preparation method of the ionic liquid-graphene oxide doped organosilicon-modified acrylic resin comprises: An initiator is added to a mixed monomer solution of methyl acrylate, styrene, hydroxyethyl methacrylate and acrylic acid, and the mixture is uniformly mixed and then dripped into a mixed solvent of polydimethylsiloxane, ethyl acetate and butyl acetate to carry out a free radical copolymerization reaction, thereby obtaining a water-based organosilicon-modified acrylic resin; The ionic liquid and graphene oxide are mixed and then ground to obtain ionic liquid-graphene oxide, and the ionic liquid-graphene oxide is added to a water-based organosilicon-modified acrylic resin and then dispersed to obtain an ionic liquid-graphene oxide-doped water-based organosilicon-modified acrylic resin.

3. The water-based heat-resistant coating according to claim 2, characterized in that: The ionic liquid contains phosphate ions.

4. The water-based heat-resistant coating according to claim 3, characterized in that: The concentration of the phosphate ions is 1% to 3%.

5. The water-based heat-resistant coating according to claim 3, characterized in that: The ionic liquid includes tributylamine phosphate or triethylamine phosphate.

6. The water-based heat-resistant coating according to claim 2, characterized in that: The mass ratio of the ionic liquid to graphene oxide is 15-30:

1.

7. The water-based heat-resistant coating according to claim 2, characterized in that: The mass ratio of the ionic liquid-graphene oxide to the water-based organosilicon-modified acrylic resin is 1:20-100.

8. The water-based heat-resistant coating according to claim 1, characterized in that: The pigment includes rutile titanium dioxide and / or carbon black; The filler includes one or more of talc powder, precipitated barium sulfate or mica powder; The anti-rust material includes an inorganic anti-corrosion material; The anti-flash rust agent includes an organic zinc chelate anti-flash rust agent; The dispersant includes a nonionic wetting dispersant; The defoamer comprises a polyether siloxane defoamer; The leveling agent includes a polyether siloxane copolymer leveling agent; The film-forming agent includes one or more of ethylene glycol, propylene glycol or dodecyl alcohol ester; The thickener includes a polyurethane thickener and / or a polyacrylic acid thickener; The organic solvent includes propylene glycol methyl ether and / or propylene glycol diacetate.

9. A method for preparing a water-based heat-resistant coating as claimed in claim 1, characterized in that: The preparation method comprises: The water, dispersant, defoamer, pigment, filler and rust-proof material are mixed evenly and then ground to a fineness of ≤30 μm to obtain a water slurry; Add water-based resin into a container, add anti-rust agent, film-forming agent, water slurry, organic solvent and leveling agent during stirring, add thickener to adjust viscosity after stirring evenly, and obtain the product.

10. Use of the water-based heat-resistant coating according to claim 1 in a rotary kiln.

Citation Information

Patent Citations

  • Oxidized graphene insulating heat-radiating coating and preparation method thereof

    CN105086688A

  • Silicon resin environment-friendly waterborne high temperature-resistant coating material as well as preparation and application thereof

    CN108977064A

  • Ionic liquid modified graphene oxide / polyisoprene composite adhesive film as well as preparation method and application thereof

    CN116041765A

  • Silicon-phosphorus ionic liquid modified graphene-PC / ABS composite material and preparation method thereof

    CN118459963A

  • Use Of A Silicone Rubber Composition For The Manufacture Of An Insulator For High Voltage Direct Current Applications

    US20170372815A1

Cited By

  • Preparation method and application of antirust coating for marine engine

    CN120248732A

  • Water-based paint for color-coated aluminum coil and preparation method of water-based paint

    CN120966335A